2017
DOI: 10.3168/jds.2016-11543
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by environment (climate) interaction improves genomic prediction for production traits in US Holstein cattle

Abstract: Genotype by environment interaction (G × E) in dairy cattle productive traits has been shown to exist, but current genetic evaluation methods do not take this component into account. As several environmental descriptors (e.g., climate, farming system) are known to vary within the United States, not accounting for the G × E could lead to reranking of bulls and loss in genetic gain. Using test-day records on milk yield, somatic cell score, fat, and protein percentage from all over the United States, we computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…Recent advances in association models have included explicit modeling of categorical G×E (Murcray et al 2009;Thomas 2010;Korte et al 2012;Marigorta & Gibson 2014;Li et al 2014;Kooperberg et al 2016;Windle 2016), but to our knowledge there are no published genome-wide association studies accounting for genotype interactions with 570 continuous environmental gradients (a reaction norm approach, cf. Jarquín et al 2014;Tiezzi et al 2017). By employing a reaction norm approach to G×E (as we did here), models can be applied to prediction at new sites, which is not possible using categorical, correlated trait approaches to G×E (Falconer 1952;Korte et al 2012) where sites are treated as idiosyncratic.…”
Section: Genotype-by-environment Interactions In Genome-wide Associatmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in association models have included explicit modeling of categorical G×E (Murcray et al 2009;Thomas 2010;Korte et al 2012;Marigorta & Gibson 2014;Li et al 2014;Kooperberg et al 2016;Windle 2016), but to our knowledge there are no published genome-wide association studies accounting for genotype interactions with 570 continuous environmental gradients (a reaction norm approach, cf. Jarquín et al 2014;Tiezzi et al 2017). By employing a reaction norm approach to G×E (as we did here), models can be applied to prediction at new sites, which is not possible using categorical, correlated trait approaches to G×E (Falconer 1952;Korte et al 2012) where sites are treated as idiosyncratic.…”
Section: Genotype-by-environment Interactions In Genome-wide Associatmentioning
confidence: 99%
“…Existing approaches to genome-wide association studies (GWAS) with G×E (sometimes referred to as genome-wide interaction studies, GWIS) have dealt with categorical nominal environments (Murcray et al 2009;Thomas 2010;125 Korte et al 2012;Gauderman et al 2013;Marigorta & Gibson 2014), benefiting from the statistical convenience of modeling phenotypes in different environments as correlated traits (Falconer 1952). Association models have not been applied to G×E along continuous environmental gradients, such as modeling SNP associations with reaction norms (Jarquín et al 2014;Tiezzi et al 2017). Despite the existence of studies where 130 fitness was measured in multiple common gardens for diverse genotyped accessions (Fournier-Level et al 2011a), studies where linkage mapping was conducted for fitness at multiple sites (Ågren et al 2013), and studies where authors conducted association mapping for G×E effects on phenotypes (Li et al 2014), we found no example of association studies of G×E for fitness, which is the basis of local adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes can vary in their response to measurable and non-measurable environmental factors, called macro-and micro-environmental sensitivity, respectively (Mulder, Rönnegård, Fikse, Veerkamp, & Strandberg, 2013). Genetic variation in macro-environmental sensitivity exists for instance in response to temperature (see Carabaño et al, 2017 for a review), seasonality (Sevillano, Mulder, Rashidi, Mathur, & Knol, 2016), disease outbreaks (Herrero-Medrano et al, 2015;Mathur et al, 2014;Rashidi, Mulder, Mathur, Arendonk, & Knol, 2014) or management level of the farm (Calus, Groen, & Jong, 2002;Hammami et al, 2009;Kolmodin, Strandberg, Jorjani, & Danell, 2003;Tiezzi, Campos, Parker Gaddis, & Maltecca, 2017). Such macro-environmental factors affect the whole farm and can be studied using reaction norms (Falconer, 1990;Lynch & Walsh, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy was expectedly low in this extreme setting, though surprisingly not very low (see the next sub-section on possible reasons). These scenarios might seem too extreme, but they are a reflection of real situation in many countries around the world (e.g., Lawrence et al, 2015) Spatial modelling has a long tradition and has been used before in animal breeding (e.g., Saebø and Frigessi, 2004;Tiezzi et al, 2017). We have used it in the extreme scenario of small herds and for this reason choose to use the geostatistical approach to use all the available information.…”
Section: Why Spatial Modelling Improves Genetic Evaluationmentioning
confidence: 99%
“…Genotype-by-environment interactions have been modelled in several studies (Strandberg et al, 2009;Hayes et al, 2009;Tiezzi et al, 2017;Yao et al, 2017;Schultz and Weigel, 2019) and such interactions are likely substantial in smallholder systems, in particular when native and exotic breeds are used (Ojango et al, 2019). We ignored these interactions in our study.…”
Section: The Limitations Of This Study and Future Possibilitiesmentioning
confidence: 99%